(untitled) (Jurnal Abdimas Administrasi Kesehatan, 2022)
Build upon it, a good governance will generate a good public services as well. Nevertheless, there are a few question while processing the enforcement practically. As occur in Puskesmas Juanda, the researcher have found a few question such as the unoptimal yet referral health services, the undistributed of health coverage, and the inadequate of facility and infrastructure along the lack quality and quantity of a health personnel resourch. This research intend to define the realization of a good governance which is implemented by Public Health Office by following the standar operation procedure (SOP) in order to realize a healthy, independent, and justice community of Puskesmas Juanda. This research implemented by Public Health Office Puskesmas Juanda on January. Focus on the implementation of principle partisipation, legal certainty, transparancy, responsiveness, oriented to concensus, justice , effectiveness, and effficiency, acountability, dan vision strategy factor that influence a governance of health services. Technique of collecting data by interview, observation, and document while information took on purposive sampling. Kind of research that used by researcher is descriptive and will be analized on qualitative. The outcome from this research known that the implementation of a good governance from Health services in Puskesmas Juanda on January, 24-25 2021 has not implemented yet due the principle of a good health service govenrnance. It is because of the Public Health Office still not able to apply the principles of effectivity and effeciency in the allocation of the human resourch and the management of health budgeting until it is difficult to administer the justice, transparancy, responsiveness pricnciple toward people needs.